2013
DOI: 10.1128/mbio.00611-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Replication of the Novel Human Betacoronavirus EMC on Primary Human Epithelium Highlights Its Zoonotic Potential

Abstract: The recent emergence of a novel human coronavirus (HCoV-EMC) in the Middle East raised considerable concerns, as it is associated with severe acute pneumonia, renal failure, and fatal outcome and thus resembles the clinical presentation of severe acute respiratory syndrome (SARS) observed in 2002 and 2003. Like SARS-CoV, HCoV-EMC is of zoonotic origin and closely related to bat coronaviruses. The human airway epithelium (HAE) represents the entry point and primary target tissue for respiratory viruses and is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
231
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(249 citation statements)
references
References 17 publications
16
231
0
2
Order By: Relevance
“…Experience from SARS-CoV showed that different regimens of interferon were used alone or in combination with ribavirin [4]. However, both IFN-a and IFN-l inhibited MERS-CoV more effectively than SARS-CoV [27]. In vitro studies also showed that the addition of IFN-b had a significant antiviral effect on MERS-CoV resulting in a 3-log reduction of the virus to undetectable levels [28].…”
mentioning
confidence: 91%
“…Experience from SARS-CoV showed that different regimens of interferon were used alone or in combination with ribavirin [4]. However, both IFN-a and IFN-l inhibited MERS-CoV more effectively than SARS-CoV [27]. In vitro studies also showed that the addition of IFN-b had a significant antiviral effect on MERS-CoV resulting in a 3-log reduction of the virus to undetectable levels [28].…”
mentioning
confidence: 91%
“…The new coronavirus seems to be fully able to penetrate human bronchial epithelia cultures. At the same time, like SARS-CoV, it appears to be sensitive to treatment with interferons (types I and III) [17]. [13].…”
Section: Virological Informationmentioning
confidence: 99%
“…Infection experiments in cell culture showed that MERS-CoV does not use the SARS-CoV receptor, angiotensin converting enzyme 2 (ACE2), for entry, and that MERS-CoV has a much broader host range than the epidemic isolate of SARS-CoV. [8][9][10][11][12][13][14] The genome structure of MERS-CoV is similar to other coronaviruses, with the 52 two-thirds of the genome encoding the non-structural proteins (NSPs) required for viral genome replication, the remaining 32 third of the genome encoding the structural genes that make up the virion (spike, envelope, membrane, and nucleocapsid proteins), and four accessory genes interspersed within the structural gene region. 2 One additional similarity between MERS-CoV and SARS-CoV is their abilities to inhibit a robust type I interferon (IFN) response in infected cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…Importantly, several studies show that MERS-CoV, similar to SARS-CoV, does not induce an early type I IFN response, suggesting that MERS-CoV may encode proteins that inhibit sensing of the viral RNA during infection. 8,11,14,15 The modulation of these pathways may explain the increased lethality of MERSCoV.…”
Section: Pathogenesismentioning
confidence: 99%